KONVERSI BATUBARA LIGNITE MENJADI ASAM HUMAT SEBAGAI PUPUK TANAMAN - Fadhilah, Rahimatul; Nursanto, Edy (Universitas Pembangunan Nasional Veteran Yogayakarta, 2024)
Low-rank coals, such as lignite and sub-bituminous coal, generally exhibit low calorific values (< 5,100 kcal/g, air-dried basis) and high moisture content (30-50%). This high moisture makes them less attractive and difficult to market, despite their abundance in Indonesia. Additionally, these coals are prone to spontaneous combustion, requiring special handling. Given their high moisture and sulfur content, they are inefficient as fuel and contribute to gas pollution, necessitating costly emission controls. This study, conducted in collaboration with Universitas Pembangunan Nasional Veteran Yogyakarta, explores the use of fine coal as a fertilizer additive. The research aims to evaluate the effectiveness of fine coal in urea fertilizers and analyze its humic acid content. Fine coal was tested as an additive in urea fertilizers at ratios of 3:1, 1:1, and 1:3 on pakcoy, kangkung, and tomatoes. The 1:3 ratio of urea to fine coal proved most effective, enhancing plant growth and leaf quantity. Results suggest fine coal, a byproduct from PT Adaro Indonesia, can be effectively used as a fertilizer additive, contributing to waste reduction. However, humic acid analysis revealed it does not yet meet standard fertilizer quality requirements, indicating a need for further improvement. Keyword: Low-rank coals, Fine coal, Fertilizer additive, Humic acid, Plant growth